Strategi Propaganda dalam Iklan Shopee Belanja Seru, Hidup Lebih Mudah - Raden Dehana Balqis; Arfian Suryasuciramdhan; Vivi Valentine; Cecinia Siburian (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The growth of digital platforms has driven significant transformations in marketing communication strategies, particularly in e-commerce advertising practices. Shopee, as one of the largest e-commerce companies in Indonesia, utilizes digital propaganda strategies through visual and audio content to shape consumer perception and behavior. The advertisement with the slogan